Improving Economic Literacy for the Young Generation of PERMAI in Penang, Malaysia: Building Entrepreneurial Skills - Arniati Arniati; Andi Hakib; Muhammad Hasan (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This Community Service Activity (PKM) was carried out in collaboration with the Indonesian Community Organization (PERMAI) Penang, Malaysia, and involved 30 participants aged 7-17 years consisting of Indonesian diaspora students and youth. The aim of this activity is to improve economic literacy and entrepreneurial skills through a participatory approach that combines theory and hands-on practice. The material provided includes personal financial management, financial planning, and the preparation of simple business ideas based on self-potential. The results of the evaluation showed a significant increase in participants' understanding, with an average post-test score of 86% compared to the pre-test. In addition to increasing knowledge and skills, this activity also strengthens the character of the participants, especially in terms of independence, entrepreneurial ethics, and social responsibility. Thus, this PKM proves that the integration of economic literacy and entrepreneurship training is effective in empowering diaspora youth to face economic challenges and create business opportunities independently.